2011
DOI: 10.1371/journal.pone.0021658
|View full text |Cite
|
Sign up to set email alerts
|

Broad Antiviral Activity of Carbohydrate-Binding Agents against the Four Serotypes of Dengue Virus in Monocyte-Derived Dendritic Cells

Abstract: BackgroundDendritic cells (DC), present in the skin, are the first target cells of dengue virus (DENV). Dendritic cell-specific intercellular adhesion molecule 3-grabbing non-integrin (DC-SIGN) is present on DC and recognizes N-glycosylation sites on the E-glycoprotein of DENV. Thus, the DC-SIGN/E-glycoprotein interaction can be considered as an important target for inhibitors of viral replication. We evaluated various carbohydrate-binding agents (CBAs) against all four described serotypes of DENV replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 68 publications
(99 reference statements)
1
47
0
1
Order By: Relevance
“…Examples of binding and entry inhibitors are maraviroc [6;7], a chemokine receptor antagonist preventing the entry of HIV, and carbohydrate-binding agents that bind to glycoproteins on the virus surface thereby preventing infection with dengue virus (DENV) [8]. DENV is one of the most important emerging viruses in tropical and subtropical countries with 2.5 billion people at risk to get infected and every year more than 50 million clinical cases of DENV infections [9].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of binding and entry inhibitors are maraviroc [6;7], a chemokine receptor antagonist preventing the entry of HIV, and carbohydrate-binding agents that bind to glycoproteins on the virus surface thereby preventing infection with dengue virus (DENV) [8]. DENV is one of the most important emerging viruses in tropical and subtropical countries with 2.5 billion people at risk to get infected and every year more than 50 million clinical cases of DENV infections [9].…”
Section: Introductionmentioning
confidence: 99%
“…Again, DC-SIGN expression on MDDC renders cells susceptible for DENV in contrast to monocytes ( Figure 7A, B). MR is also present on monocyte-derived DC (MDDC) and anti-MR antibodies can inhibit DENV infection, although to a lesser extent than anti-DC-SIGN antibodies do ( Figure 7C) [61]. Furthermore, the combination of anti-DC-SIGN and anti-MR antibodies was even more effective in inhibiting DENV infection.…”
Section: Role Of Dc-sign In Denv Infectionmentioning
confidence: 98%
“…This activation is induced by TNF-and IFN-secreted by DENV-infected DC [40,89,90]. Instead, Alen et al observed an upregulation of the costimulatory molecules CD80 and CD86 and a downregulation of DC-SIGN and MR on the total (uninfected and infected) DC population following DENV infection [61]. This could indicate that the DC are activated and can interact with naive T-cells and subsequently activate the immune system resulting in increased vascular permeability and fever.…”
Section: Broad Antiviral Activity Of Cbas Against Denvmentioning
confidence: 99%
See 1 more Smart Citation
“…68,69 However, plant lectins are not orally bioavailable, sensitive for proteolytic cleavage, and expensive to produce. These shortcomings pose a significant challenge with respect to their development.…”
Section: Acs Infectious Diseasesmentioning
confidence: 99%